The effect of chemical activators on early strength of ordinary Portland cement-slag mortars - Sajedi, F.; Razak, Hashim Abdul (Elsevier, 2010)
Although the use of slag has many benefits, its low hydration at early stages causes the strength to be low. Hence, the uses of slag are restricted, even before it needs to be activated. In this investigation, a chemical method was used to activate the ordinary Portland cement-slag mortars (OSM). 37 OSM were used, 4 of them as control. All mix designs were made by W/B = 0.33, S/B = 2.25, and with 0, 30, 40, 50, and 60 levels of slag. The activators; sodium hydroxide, potassium hydroxide, and sodium silicate have been used. Whenever the activators were used alone, the highest effect was obtained by sodium silicate and the lowest for sodium hydroxide. It was determined that the effects of the combined activators are better than that of an individual one. It was observed that strength loss for some mixes, at long ages, is determined by some factors, such as level of slag used, type and dosage of alkali activators, and curing regimes.